2021
DOI: 10.3847/1538-4357/ac0d55
|View full text |Cite
|
Sign up to set email alerts
|

A Disk and No Signatures of Tidal Distortion in the Galaxy “Lacking” Dark Matter NGC 1052-DF2

Abstract: Using ultra-deep imaging (µ g = 30.4 mag/arcsec 2 ; 3σ, 10 ×10 ), we probed the surroundings of the first galaxy "lacking" dark matter KKS2000[04] (NGC 1052-DF2). Signs of tidal stripping in this galaxy would explain its claimed low content of dark matter. However, we find no evidence of tidal tails. In fact, the galaxy remains undisturbed down to a radial distance of 80 arcsec. This radial distance triples previous spatial explorations of the stellar distribution of this galaxy. In addition, the distribution … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 65 publications
4
28
0
Order By: Relevance
“…We note here thatMontes et al (2021) interpret the elongation on the outskirts of NGC 1052-DF2 as a disk.…”
mentioning
confidence: 61%
See 1 more Smart Citation
“…We note here thatMontes et al (2021) interpret the elongation on the outskirts of NGC 1052-DF2 as a disk.…”
mentioning
confidence: 61%
“…Taking into account that their metallicity content follows the usual stellar mass-metallicity relation for dwarf galaxies (Fensch et al 2019;Ruiz-Lara et al 2019), the possibility that they are tidal dwarf galaxies -galaxies formed by strong interactions with recycled material from massive host galaxies, high in metals, and intrinsically born with a lack of dark matter (see e.g., Duc 2012;Román et al 2021) -is ruled out. The properties of these LSBGs have been the subject of much debate (see e.g., Martin et al 2018;Ogiya 2018;Famaey et al 2018;Kroupa et al 2018;Lewis et al 2020;Haslbauer et al 2019;Müller et al 2019;Nusser 2019;Montes et al 2020Montes et al , 2021. One hypothesis put forward by Trujillo et al (2019) is that these LSBGs "lacking dark matter" could be at a closer distance than initially estimated by van Dokkum et al (2018avan Dokkum et al ( , 2019a.…”
Section: Introductionmentioning
confidence: 99%
“…Amorisco et al (2018) found that, even in UDGs with abundant GC systems, 𝑅 GC /𝑅 e < 2 with high probability, with several systems better described by 𝑅 GC /𝑅 e 1. More recent estimates of 𝑅 GC for DF44 7 (Saifollahi et al 2021), for MATLAS-2019 (Müller et al 2021) and for NGC1052-DF2 (Montes et al 2021) find 𝑅 GC ≤ 𝑅 e . Again, due to statistical uncertainties, we opt first to work with the composite sample.…”
Section: Gc Distributionmentioning
confidence: 94%
“…It has recently been suggested that DF2 and DF4 are entirely unrelated, with DF4 being stripped of its dark matter by NGC 1035, which is near it in projection, and DF2 a face-on disk galaxy with a normal dark-matter content 46 , 47 . The association of DF4 with NGC 1035 is not seen in all datasets 21 , and there is no compelling evidence that DF2 is a disk 7 .…”
Section: Methodsmentioning
confidence: 99%